Awareness of Rhythm Patterns in Speech and Music in Children with Specific Language Impairments - Cumming, Ruth; Wilson, Angela; Leong, Victoria; Colling, Lincoln J.; Goswami, Usha (Frontiers in Human Neuroscience, 2015)
Children with specific language impairments (SLIs) show impaired perception and production of language, and also show impairments in perceiving auditory cues to rhythm (amplitude rise time [ART] and sound duration) and in tapping to a rhythmic beat. Here we explore potential links between language development and rhythm perception in 45 children with SLI and 50 age-matched controls. We administered three rhythmic tasks, a musical beat detection task, a tapping-to-music task, and a novel music/speech task, which varied rhythm and pitch cues independently or together in both speech and music. Via low-pass filtering, the music sounded as though it was played from a low-quality radio and the speech sounded as though it was muffled (heard “behind the door”). We report data for all of the SLI children (N = 45, IQ varying), as well as for two independent subgroupings with intact IQ. One subgroup, “Pure SLI”, had intact phonology and reading (N=16), the other, "SLI PPR" (N=15), had impaired phonology and reading. When IQ varied (all SLI children), we found significant group differences in all the rhythmic tasks. For the Pure SLI group, there were rhythmic impairments in the tapping task only. For children with SLI and poor phonology (SLI PPR), group differences were found in all of the filtered speech/music AXB tasks. We conclude that difficulties with rhythmic cues in both speech and music are present in children with SLIs, but that some rhythmic measures are more sensitive than others. The data are interpreted within a ‘prosodic phrasing’ hypothesis, and we discuss the potential utility of rhythmic and musical interventions in remediating speech and language difficulties in children.